(untitled) (ModaPalavra e-periódico, 2021)
Numerous studies are carried out every year in order to discover innovative ways of making textiles for comfort, safety and, often, that represent the ideologies of the consumer. However, due to the textile industry’s problems related to environmental degradation, researchers have conducted studies on materials and processes that are more sustainable. Therefore, this article proposes a bibliographic review of an analytical character, in three databases, the Scopus, ScienceDirect and ProQuest, on more sustainable materials and processes used in the textile sector between the periods of 2015 and 2020. The results show 38 articles on sustainable alternatives of materials and processes for the current market, as well as on-going research on new possibilities for textiles in the fields of engineering, biotechnology, design, among others.